If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying 15x + 6y = 18 Solving 15x + 6y = 18 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6y' to each side of the equation. 15x + 6y + -6y = 18 + -6y Combine like terms: 6y + -6y = 0 15x + 0 = 18 + -6y 15x = 18 + -6y Divide each side by '15'. x = 1.2 + -0.4y Simplifying x = 1.2 + -0.4y

| lograizx=log(x-2) | | y+12=x^2+x | | lnx+2=1 | | tan(x)-3=-4 | | 5t^2+t=0 | | x^2+y^2-2x-2y=0 | | 16x-3x=3 | | x^2-y^2+4x-4y=0 | | 8m=4.4 | | 4x+2y=2x+4y-2 | | 10x-12=12x-10 | | x^2=6+x | | 6x+x^2=9 | | t^2+6t-15=0 | | x/6=8 | | 5(x-1)= | | 2x=6+3x | | x-38=27 | | k/4+1=9 | | 4x(x+2)=20-x | | (-x+7)-x=5x | | 4(x+2)=20-x | | 2(50-2)=x | | 4x(x-4)=12 | | 5x^2+8=0 | | 1/12=456 | | 1/12=1/456 | | (3x-1)(x+8)= | | 4x-4=28x+14 | | 49x^2+1=49 | | 7x+8=5x+32 | | 4a^2+b^2=12 | | y^5-1=0 | | 7r-4(4r+8)=24 | | 6x^4-24x^2-54=0 | | x^4-4x^2-9=0 | | 3x(x+3)=26 | | 11+-2c=4+5c | | 6(x+9)+5=59 | | 4x-3=6x+8 | | 2w-3+3(w-4)=-5(w-6) | | .66x+1.33=-66 | | 50.5(0.3m+35n)=0.8(-0.09n-22m) | | .66x+1.33=-.66 | | 0.08(0.3m+35n)=0.8(-0.09n-22n) | | 0.05(0.3m+35n)=0.8(-0.09n-22m) | | 1+c=3 | | (3x-8)(x+6)= | | 12w^2-13w=35 | | 40=r(r-3) | | 2y+5*2= | | 3x-2=-5x | | 12u^3+4u^2-96u= | | 2x+6=8x | | (4x)(2x)= | | X^2+3x=175 | | X^2+x=175 | | 175=x^2+3x | | n+(n+2)+(n+4)=39 | | 4x-3-8x+1=-5x=9 | | -2(w+9)=8w-8 | | 8c+16d=14000 | | 63+x=-22 | | 6y-36=2(y+2) | | 4*5-3-8*5+1=-5*5+9 |